2015
DOI: 10.1111/sms.12545
|View full text |Cite
|
Sign up to set email alerts
|

A new equation to estimate temperature‐corrected PaCO2 from PETCO2 during exercise in normoxia and hypoxia

Abstract: End-tidal PCO2 (PET CO2 ) has been used to estimate arterial pressure CO2 (Pa CO2 ). However, the influence of blood temperature on the Pa CO2 has not been taken into account. Moreover, there is no equation validated to predict Pa CO2 during exercise in severe acute hypoxia. To develop a new equation to predict temperature-corrected Pa CO2 values during exercise in normoxia and severe acute hypoxia, 11 volunteers (21.2 ± 2.1 years) performed incremental exercise to exhaustion in normoxia (Nox, PI O2 : 143 mmHg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…65 Therefore, it is reasonable assuming that the diameter of the MCA was not changed in Study I by the 6 mmHg decrease and increase in P ET CO 2 , during the sprint and recovery, respectively, assuming that P ET CO 2 is a good surrogate of PaCO 2 . 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Therefore, it is reasonable assuming that the diameter of the MCA was not changed in Study I by the 6 mmHg decrease and increase in P ET CO 2 , during the sprint and recovery, respectively, assuming that P ET CO 2 is a good surrogate of PaCO 2 . 31…”
Section: Discussionmentioning
confidence: 99%
“…Part of the results on oxygen transport and pulmonary gas exchange obtained during the invasive experiments has been reported. 26,31,32 Since 7 ml (kg body mass) −1 of carbon monoxide (CO) was administered at exhaustion during the last incremental exercise test, a small amount of CO was present in blood at the start of the Wingate test. 26…”
Section: Methodsmentioning
confidence: 99%
“…(1) P a CO 2tc = 8.607 + 0.716 x P ET CO 2 [33]. The relationship between P a CO 2 and P ET CO 2 under dive conditions was examined in a study by Mummery, et al, which found that in a dry hyperbaric chamber at 2.8 ATA, the end-tidal arterial PCO 2 difference was smaller at depth versus the surface under both resting and exercising conditions.…”
Section: Measuring Hypercapnia In Divingmentioning
confidence: 99%
“…Some clinical investigations have demonstrated that P ET CO 2 can indirectly reflect P a CO 2 . 11,12 Under normal conditions, P ET CO 2 is lower than P a CO 2 by 3-6 mmHg. 13 At an altitude of 3000 m, the atmospheric pressure of our hospital is 532 mmHg and the P a CO 2 is 34 mmHg, resulting in a calculated P ET CO 2 of 28-31 mmHg.…”
Section: Discussionmentioning
confidence: 94%